(untitled) (Naturalistic: Jurnal Kajian dan Penelitian Pendidikan dan Pembelajaran, 2020)
This research is about how to manage of reading and writing Al-Qur’an in Madrasah Ibtidaiyah Plus Ja-alhak Bengkulu. This research method is descriptive qualitative, that is analyzing and presenting facts systematically. With the aim of systematically and accurately describing the facts and characteristics of the management of Koran reading and writing in Madrasah Ibtidaiyah Plus Ja-Alhak. The result of this research is the learning management of reading al-Qur’an especially in MI Plus Ja-alhak has been running well, proved by the learning process which is in accordance with the existing teaching system such as: introductory activity, core activities and cover of learning. In addition, the evaluation of learning for both students and teachers is conducted regularly. The evaluation model implemented in MI Plus Ja-alhak Bengkulu is an effort to support the improvement of the quality of learning which includes the quality of students and the quality of teachers.